Knowledge, Attitudes, and Practices of Iraqi Parents Regarding Antibiotic Use in Children and the Implications - Omeed Darweesh; Amanj Kurdi; Marwan Merkhan; Hemn Ahmed; Salih Ibrahem; Radhwan N. Al-Zidan; Johanna C. Meyer; Brian Godman (Antibiotics)
Background: Antibiotic misuse is a major global health issue, particularly in low- and middle-income countries (LMICs), where inappropriate use contributes to antimicrobial resistance (AMR). Inappropriate antibiotic use is exacerbated in LMICs by pressure from parents on physicians and pharmacists to prescribe and dispense antibiotics for their children, often for viral infections. There is currently limited knowledge of key issues in Iraq to improve future antibiotic use. Consequently, we explored knowledge, attitudes, and practices (KAPs) of Iraqi parents regarding antibiotic use in their children to provide future direction. Methods: A cross-sectional survey was conducted between November 2023 and September 2024 among 1878 parents in four districts of Iraq. A structured questionnaire assessed parents’ KAPs towards antibiotic-related uses and practices. Data were analyzed using descriptive statistics and Chi-square tests to examine the associations between demographic variables and KAP indicators. Results: Among the participants, 83% were aware that antibiotics are ineffective for viral infections, and 75% recognized potential side effects from antibiotics. Despite this knowledge, 63% of parents admitted to administering antibiotics to their children without a prescription, with 42% discontinuing treatment once symptoms improved. Factors including cost, dosage, and taste influenced antibiotic selection. Parents with higher education and income levels were more likely to engage in self-medication. Pharmacists were the primary source of antibiotic information for 52% of respondents. Conclusions: Despite adequate knowledge, inappropriate practices such as self-medication and discontinuing treatment early were prevalent. Targeted educational campaigns, particularly among parents with higher education levels and incomes, are necessary to mitigate AMR in Iraq.